(untitled) (Journal of Medical & Health Sciences Review, 2025)
The increasing resistance of bacterial pathogens to conventional antibiotics has led to a growing interest in natural antimicrobial agents. Allium sativum (garlic) is widely recognized for its medicinal properties, particularly its antibacterial effects. This study aimed to evaluate the antibacterial activity of garlic extract against Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative) using the agar well diffusion and broth dilution methods. The results revealed that garlic extract exhibited a stronger antibacterial effect against S. aureus, with inhibition zones of 9.5 ± 0.3 mm, 12.3 ± 0.4 mm, 15.0 ± 0.5 mm, and 18.2 ± 0.4 mm at concentrations of 10 mg/mL, 25 mg/mL, 50 mg/mL, and 100 mg/mL, respectively. In contrast, E. coli showed lower susceptibility, with inhibition zones of 7.8 ± 0.5 mm, 10.5 ± 0.3 mm, 13.2 ± 0.4 mm, and 15.6 ± 0.6 mm at the same concentrations. The Minimum Inhibitory Concentration (MIC) values were 8 mg/mL for S. aureus and 16 mg/mL for E. coli, while the Minimum Bactericidal Concentration (MBC) values were 16 mg/mL and 32 mg/mL, respectively, indicating that E. coli required a higher concentration for bacterial killing. Phytochemical analysis confirmed the presence of flavonoids (2.5 ± 0.2 mg/g), tannins (1.8 ± 0.1 mg/g), saponins (3.2 ± 0.3 mg/g), alkaloids (2.1 ± 0.2 mg/g), and glycosides (1.5 ± 0.2 mg/g), which contribute to the antimicrobial effects of garlic. The presence of these bioactive compounds suggests that garlic extract exerts its antibacterial effects by disrupting bacterial cell membranes and inhibiting essential bacterial enzymes. The MIC to MBC ratio for S. aureus (2.0) and E. coli (2.0) indicated a bactericidal effect of garlic extract on both bacterial strains. Compared to the standard antibiotic ciprofloxacin (5 µg/mL), which exhibited inhibition zones of 26.5 ± 0.5 mm for S. aureus and 24.3 ± 0.4 mm for E. coli, garlic extract showed lower but significant antibacterial activity. These findings suggest that Allium sativum extract possesses strong antibacterial properties, particularly against Gram-positive bacteria, and may serve as a natural alternative or complementary treatment for bacterial infections. Future research should focus on isolating specific active compounds, optimizing extraction methods, and exploring their synergistic effects with antibiotics to enhance antibacterial efficacy, particularly against antibiotic-resistant pathogens.